Development of Website-Based Interactive E-Modules with Project Based Learning Learning Models to Increase Student Learning Interest in PKWU Subjects in Vocational High Schools - Bambang Sujatmiko; Madelin Christina Purba (Jurnal Ekonomi dan Bisnis Digital, 2023)
To share knowledge between professors and students, learning media is a common format. It is necessary to modify the learning materials to suit the requirements of different academic fields. There are several issues with this study, including the fact that the only learning resources used in schools are LKS (Student Worksheets) and limited LCD resources, the requirement for practice in the Creative Products and Entrepreneurship (C3) subjects, and the fact that schools use a moving class system, all of which make it necessary for students to access information using more efficient learning resources. The ADDIE-type development model was used to perform this research utilizing the research and development (RnD) methodology. The distribution of learning interest questionnaires among students and the results of student psychomotor skills assessments, which take the form of Pretest-Posttest Control Group Design, both serve to gauge student interest in learning. The findings of the hypothesis test were obtained following the conclusion of the study, and they are as follows. There were variations in students' psychomotor skills before and after utilizing the web-based interactive e-module learning environment with a project-based learning paradigm, as shown by the statistical sig (2 tailed) = 0.00, where 0.00 0.05 (significant threshold). Class XI Multimedia 1 contributed 45.74% of the increase, and class XI Multimedia 2 contributed 46.78%. Additionally, it was mentioned that the examination of student learning interest in created media revealed that the experimental class had very high levels of student learning interest, with 88.33% of students showing interest in materials 1 and 90